Enhancement of cisplatin-induced apoptosis by infection with adeno-associated virus type 2 - Duverger, Valerie; Krammer, Peter H.; Schlehofer, Jörg R. (International journal of cancer, 2002)
The non-pathogenic human adeno-associated virus, AAV, has been shown to sensitize human cancer cells and experimental tumors towards the action of chemotherapeutic agents such as cisplatin. Since chemotherapeutic drugs mainly involve the induction of apoptosis, we investigated whether 1 possible mechanism of AAV-mediated sensitization of human tumor cells may result from an enhancement of cisplatin-induced apoptosis. In HeLa and A549 cells, infection with AAV type 2 (AAV-2) increased cisplatin-induced DNA fragmentation but had no cytotoxic effect by itself. This enhanced apoptosis appeared to be mediated at least in part by a component of the viral capsid since empty or UV-inactivated AAV-2 particles were also able to boost cisplatin-induced DNA fragmentation. Interestingly, these effects were not observed after infection with AAV type 5 (AAV-5) or the autonomous parvovirus, H-1. AAV-2-mediated enhancement of apoptosis was not associated with a modification of the expression of CD95 ligand, CD95 receptor or other death receptors, as shown by RT-PCR and RNase protection assay. In contrast, using the mitochondrial fluorescent dye, JC-1 in flow cytometry, AAV-2 infection was found to further reduce the mitochondrial transmembrane potential after treatment with cisplatin in a caspase-independent manner, suggesting that increase of apoptosis by AAV-2 occurred at the mitochondrial level. In contrast, in cells of the small cell lung cancer line, P693, an enhancement of cisplatin-induced DNA fragmentation was not observed after infection with AAV-2. In these cells, sensitization to cisplatin-toxicity was associated with cell cycle arrest in G2/M. The data indicate that in the absence of viral gene expression, AAV-2-mediated sensitization to cisplatin involves multiple cellular pathways promoting cell death signals in a cell type-dependent manner. The results further support that AAV-2 particles may be appropriate adjuvants for improving cancer chemotherapy and may also have consequences regarding AAV-2-based vectors for gene therapy. © 2001 Wiley-Liss, Inc.
First published: 31 October 2001
Gesehen am 20.04.2021